Material history of bridal wear in Philippine Catholic and Christian wedding culture - Oxales, Sarah Angelica C.
Abstract The research study aimed to trace the historical development of the bridal costume in relation to the ritual celebrations practiced in Philippine urbanized settings. A survey of bridal gown trends and both customary and traditional Catholic and Christian wedding practices was gathered from photograph and archival research. The photographs collected of wedding gowns from online open calls, publications and books were catalogued chronologically, describing various garment details. Literature on weddings in the Philippines from theses, journals, books and online sources, as well as interviews with bridal gown designers and wedding planners were used to gather data on wedding rituals and personal observations on bridal gown trends. Personal communication with current stakeholders in both the bridal wear and wedding industries was used to clarify and elaborate on the data gathered. This information was categorized by decade and trends were identified by the frequency they appeared in each decade. Trends were then plotted on a parallel timeline and supplemented with illustrations. Recurring themes that indicate correlation were observed, in order to infer the relationship between the bridal costume and the wedding ritual. Using classical Sociological and Economic theories drawn from Marx (1859), Veblen (1899), and Simmel, the researcher determined correlations between the gown as a specimen of material history within the social world of Philippine Urban wedding culture. Bridal gown trend appeared to change faster the wedding ritual due to their adherence to fashion trends while wedding rituals trends lasted for 2-5 decade before changing. It was observed that changes in either bridal gowns or wedding rituals were not from direct causality, but were influenced by a third general theme. Several themes such as tradition, conservatism, the pursuit of beauty, weddings as a production, and global trends were forces which affected the change in trends of both bridal gowns and wedding rituals.